2020
DOI: 10.1002/emp2.12329
|View full text |Cite
|
Sign up to set email alerts
|

Does academic practice protect emergency physicians against burnout?

Abstract: By JACEP Open policy, all authors are required to disclose any and all commercial, financial, and other relationships in any way related to the subject of this article as per ICMJE conflict of interest guidelines (see www.icmje.org). The authors have stated that no such relationships exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 48 publications
(87 reference statements)
1
18
1
Order By: Relevance
“…40,41 professional fulfillment. [42][43][44] Given that residents are at the earliest stages of their career, it may be key to provide trainees the opportunities to explore different aspects of EM to discover where they find meaning and alignment with their passion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 professional fulfillment. [42][43][44] Given that residents are at the earliest stages of their career, it may be key to provide trainees the opportunities to explore different aspects of EM to discover where they find meaning and alignment with their passion.…”
Section: Discussionmentioning
confidence: 99%
“…The academic work environment also had a significant and comparatively large impact on resident wellness and burnout. While there are no previous data examining the relationships between burnout and elective time and academic pursuits among EM residents, multiple studies among EM faculty have shown that working in an academic environment was protective against burnout and improved professional fulfillment 42‐44 . Given that residents are at the earliest stages of their career, it may be key to provide trainees the opportunities to explore different aspects of EM to discover where they find meaning and alignment with their passion.…”
Section: Discussionmentioning
confidence: 99%
“…Spending time on meaningful work outside of direct clinical care has been shown to decrease the risk of burnout and increase career satisfaction. 10 Resources for scholarship, additional didactic education, and mentorship opportunities enable fellows to begin to cultivate their niche and jump-start their career. Attending fellowship in an environment primed for scholarship (e.g., research librarians, statisticians) allows fellows to use fellowship time to establish a foothold of scholarly productivity.…”
Section: Benefits Of Fellowshipmentioning
confidence: 99%
“…Communities also benefit from local GME program development through utilization of the program as a recruitment and retention strategy for the local physician population. Teaching physicians have greater overall satisfaction and lower rates of burnout as compared to non-teaching physicians [66][67][68][69][70]. It is estimated that 50% of the physicians presently practicing in the USA suffer symptoms of burnout [71,72].…”
Section: Reducing Burnout and Physician Turnovermentioning
confidence: 99%
“…Educating students, residents, and fellows allows providers to connect with core values from their training has been shown to reduce burnout by as much as 25%, though such teaching efforts need to be supported with an equivalent reduction in productivity expectations to generate this benefit. [65][66][67][68][69][70] Learners describe the training experiences within a community as one of the most important factors in choosing to settle in that area, particularly in rural areas. [77] Therefore, teaching responsibilities may serve as a potent recruitment and retention strategy [78].…”
Section: Reducing Burnout and Physician Turnovermentioning
confidence: 99%